2021
DOI: 10.1039/d1ra02898g
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism for secondary structure determination of proteins with unfolded domains using a self-organising map algorithm SOMSpec

Abstract: Circular dichroism secondary structure fitting by analysing derandomized spectra using the SOMSpec approach then regenerating data for the original spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
1
4
0
2
Order By: Relevance
“…In aggregate, the data demonstrate the ability of the hydrogels to release DOX in its active form through photothermal modulation. These data together with prior reports of the photothermally induced release of active proteins from hydrogels and of protein stability up to 60 °C , bode well for the potential of our hydrogels as a delivery system for a wide array of therapeutic agents.…”
Section: Resultssupporting
confidence: 67%
“…In aggregate, the data demonstrate the ability of the hydrogels to release DOX in its active form through photothermal modulation. These data together with prior reports of the photothermally induced release of active proteins from hydrogels and of protein stability up to 60 °C , bode well for the potential of our hydrogels as a delivery system for a wide array of therapeutic agents.…”
Section: Resultssupporting
confidence: 67%
“…In particular, shifts of wavelength maxima and loss of spectral intensity at high wavenumbers or low wavenumbers indicate, respectively, low helix and low sheet content in the prediction. We also found that proteins such as lysozyme and papain which have β II characteristics in their CD spectra (Whitmore et al, 2011;Olamoyesan et al, 2021) have helix-like IR spectra. Finally, proteins with prosthetic groups which absorb in the Amide I region such as flavins and hemes may also cause errors in secondary structure predictions.…”
Section: Discussionmentioning
confidence: 58%
“…The problem classes are again 1) high helix content proteins especially those with papain (S19) and/or lysozyme (S12) among their BMUs (the helix content is significantly underestimated), 2) β II proteins in particular trypsin (S24) and chymotrypsin (S25), and 3) the largely unfolded bungarotoxin (S30). Interestingly, both lysozyme and papain CD spectra (Whitmore et al, 2011;Olamoyesan et al, 2021) have β II characteristics suggesting this is a key to the problems with the first two types.…”
Section: Solid-state Protein Ir Spectra Loovmentioning
confidence: 99%
“…This reduction in peak intensity at 265 nm is proportional to the distortion due to a decrease in DNA/RNA base stacking. 28 Comparison of the CD spectrum of hnRNPB1 (1−195) and hnRNPB1 (1−278) shows the presence of a disordered structure in the LCD, which is evident by the shift of a negative maximum at 217 nm (β-sheet) toward 200 and 195 nm positive peak, which is also smaller than that expected 29 (Figure S15B). This region of LCD (195−278) used in our studies lacks structural order, evidenced by previous structural studies.…”
Section: Biochemistrymentioning
confidence: 99%